Pengaruh Motivasi Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan pada Perawat RS PKU Muhammadiyah Gamping - Melinda Kartikaningrum; Nany Noor Kurniyati (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to determine the effect of Work Motivation (X1) and Work Environment (X2) on Employee Performance (Y). This is a quantitative study. The population in this research consists of nurses at RS PKU Muhammadiyah Gamping, with a sample of 72 respondents. Data collection was conducted using a questionnaire with a Likert scale. The data analysis methods used include classical assumption tests (normality test, multicollinearity test, heteroscedasticity test), multiple linear regression analysis, and hypothesis testing (t-test, F-test, and R² test). The analysis results show the significance level of Work Motivation (X1) and Work Environment and whether they have an effect on Employee Performance. Based on the t-test results: (1) The effect of Work Motivation (X1) shows a value of 2.071 with a significance of 0.042 < 0.05, indicating that Work Motivation (X1) has a significant effect on Employee Performance (Y) at RS PKU Muhammadiyah Gamping. (2) The effect of Work Environment (X2) shows a value of 4.766 with a significance of 0.000 < 0.05, indicating that the Work Environment (X2) has a significant effect on Employee Performance (Y). The F-test results show that Work Motivation (X1) and Work Environment (X2) together significantly affect Employee Performance (Y), with an F-value of 38.247 and a significance level of 0.000 < 0.05, indicating a simultaneous significant effect on Employee Performance (Y) among nurses at RS PKU Muhammadiyah Gamping.